Charlemagne's defeat in the Pyrenees : the Battle of Rencesvals - Irujo, Xabier (Early medieval North Atlantic., 2021)
The Battle of Rencesvals is the one of the most dramatic historical event of the entire eighth century, not only in Vasconia but in Western Europe. This monograph examines the battle as more than a single military encounter, but instead as part of a complex military and political conquest that began after the conquest of the Iberian Peninsula in 711 and culminated with the creation of the Kingdom of Pamplona in 824. The battle had major (and largely underappreciated) consequences for the internal structure of the Carolingian Empire. It also enjoyed a remarkable legacy as the topic of one of the oldest European epic poems, La Chanson de Roland. The events that took place in the Pyrenean pass of Rencesvals (Errozabal) on 15 August 778 defined the development of the Carolingian world, and lie at the heart of the early medieval contribution to the later medieval period. Bron: Flaptekst, uitgeversinformatie.